Soil sealing footprint as an indicator of dispersed urban growth: a multivariate statistics approach - Tombolini, Ilaria; Munafò, Michele; Salvati, Luca (Urban research & practice, 2016)
The present study introduces a set of indicators derived from high-resolution land-use maps with the aim to illustrate the spatial distribution, intensity, and diversity of sealed soils in a Mediterranean region (Rome, Italy) shifting from a mono-centric spatial organization toward a dispersed urban agglomeration. A multivariate approach provides a comprehensive assessment of Rome 'sealing footprint', classifying local districts according to different imperviousness profiles. Results illustrate the rearrangement of the land-use structure determined by suburbanization with higher soil consumption and lower land-use efficiency. The approach is considered a promising tool to inform policies for a spatially balanced and land-saving urban development.